Inactivation of N-Acetylglucosaminyltransferase I and α1,3-Fucosyltransferase Genes in Nicotiana tabacum BY-2 Cells Results in Glycoproteins With Highly Homogeneous, High-Mannose N-Glycans - Herman, Xavier; Far, Johann; Courtoy, Adeline; Bouhon, Laurent; Quinton, Loïc; De Pauw, Edwin; Chaumont, François; Navarre, Catherine (Frontiers in Plant Science, 2021)
Nicotiana tabacum Bright Yellow-2 (BY-2) suspension cells are among the most commonly used plant cell lines for producing biopharmaceutical glycoproteins. Recombinant glycoproteins are usually produced with a mix of high-mannose and complex N-glycans. However, N-glycan heterogeneity is a concern for the production of therapeutic or vaccine glycoproteins because it can alter protein activity and might lead to batch-to-batch variability. In this report, a BY-2 cell line producing glycoproteins devoid of complex N-glycans was obtained using CRISPR/Cas9 edition of two N-acetylglucosaminyltransferase I (GnTI) genes, whose activity is a prerequisite for the formation of all complex N-glycans. The suppression of complex N-glycans in the GnTI-knocked out (KO) cell lines was assessed by Western blotting. Lack of β1,2-xylose residues confirmed the abolition of GnTI activity. Unexpectedly, α1,3-fucose residues were still detected albeit dramatically reduced as compared with wild-type cells. To suppress the remaining α1,3-fucose residues, a second genome editing targeted both GnTI and α1,3-fucosyltransferase genes (FucT). No β1,2-xylose nor α1,3-fucose residues were detected on the glycoproteins produced by the GnTI/FucT-KO cell lines. Absence of complex N-glycans on secreted glycoproteins of GnTI-KO and GnTI/FucT-KO cell lines was confirmed by mass spectrometry. Both cell lines produced high-mannose N-glycans, mainly Man5 (80 % and 86%, respectively) and Man4 (16% and 11%, respectively). The high degree of N-glycan homogeneity and the high-mannose N-glycosylation profile of these BY-2 cell lines is an asset for their use as expression platforms.